Desain Penyelesaian Kredit Macet Dalam Pembiayaan Murobahah Di BMT Bina Ummat Sejahtera - Supriyadi, Supriyadi (TAWAZUN: Journal of Sharia Economic Law, 2018)
Financing based on Islamic principles actually to increase employment opportunities and economic prosperity in accordance with the Islamic values. The existence of BMT run financing based on Islamic principles not only for profits and enliven the financing business in Indonesia, but also to create a safe business environment with Islamic principles that do not burden the debtor. One of the financing with the principles of Syariah is financing with the murabahah system. Murabahah financing is a type of purchase contract item with the acquisition price and profit (margin) as agreed by the seller and the buyer where the refund loans by the customer can be done in the form of a mortgage or loan. Loans granted certainly has risk so required ability and effectiveness in managing credit risk and minimize the potential losses. Experienced credit risk is a breakdown of murabahah financing so that need to design a settlement in such financing.